The Role of Mothers in Providing Sexual Education to Teenage Children as a Preventive Measure for Unwanted Pregnancy in Kelurahan Bandulan - Canthika, Lidia Mutiara; Dayati, Umi; Raharjo, Kukuh Miroso (Universitas Negeri Malang, 2024)
Sexual education is the teaching that children must receive about sex, sexuality and sexuality to face things that might happen in the future as they get older. Sexual education is a basic family lesson to be taught to children. The mother is the parental figure in the family who will teach sexual education because of the closeness between mother and child. Researchers conducted research on the role of mothers in providing sexual education to teenage children as a preventive measure for experiencing unwanted pregnancies. The aim of this research is to find out how mothers provide sexual education to teenage children and find out what preventive steps mothers can take so that their children avoid unwanted pregnancies. The method used in this research is qualitative with a case study type of research. From the research results obtained, the sexual education given by mothers to teenage children to prevent unwanted pregnancies has been received by children, but not comprehensively, even though sexual education is fundamental education. In research, mothers do provide sexual education to children, but only briefly, even though this sexual education is what provides children when they have to consider something and make responsible decisions regarding sex, sex and sexuality. Keywords: Mothers Role; Sexual Education; Teenager; Unwanted Pregnancy